Regional Disparities of Electoral Behaviour in Poland: Comparative Spatial Analysis - I. Yu. Okunev; Ju. S. Gorelova; E. E. Gruzdeva (Сравнительная политика)
This article refers to the topic of parliamentary elections inPoland. The authors maintain the hypothesis that more and less stable regional clusters of electoral behavior, which undergo some changes over time, exist inPoland. The study traces a pattern between the formation of regional clusters and a number of factors, such as their proximity to the borders of other states, ideological orientation of the party programs, the traditions of political culture that have developed in the regions and the division of regions into urban and rural. The study uses Moran’s index to describe the neighborhood effect. Local clusters of spatial association were calculated by means of local Moran’s index. Maps of cluster locations were constructed on the basis of the results of the 2007-2019 parliamentary elections. This allowed us to consider their spatial changes in perspective. The novelty of the work consists in use of the mathematical method of spatial autocorrelation in electoral study and consideration of the results both from the point of view of the percentage ratio and neighborhood index. It was concluded that some regional clusters remain stable throughout four electoral cycles, however, they undergo minor changes. Most of these clusters are located in rural areas. As a rule, cities are not included in stable clusters, they form separate centers, distinguished by the variety of the electoral preferences of citizens. The four analyzed electoral cycles show a tendency of reduction of the spatial dependence between the results of voting in constituencies and stability of regional clusters inPoland.